Characterization of household food waste in Italy: Three year comparative assessment and evaluation of seasonality effects. (1st June 2023) - Grant, Federica; Di Veroli, Jacopo Niccolò; Rossi, Laura
Highlights: Food categories most wasted in Italy are fruit, vegetables, bread, milk and yogurt. Larger town areas, 1 member families, and who have a low income wasted more. Retired people and families with children wasted less. This assessment poses the basis for a surveillance system on food waste in Italy. Educational campaigns for specific target groups should be developed. Abstract: In the present paper, the results of the first comparative assessment of household food waste in Italy are reported with a timeframe of three years coupled with an evaluation of seasonality effects. To pursue the aim of Sustainable Development Goal 12.3 to halve consumer food waste by 2030, the Italian Observatory on Food Surplus, Recovery and Waste carried out two surveys in 2021 (July and November) to characterize household food waste and to evaluate the seasonality effects. Data were collected with a validated questionnaire. For monitoring purposes, data collected in July 2021 were compared with those collected in July 2018. In three years, waste increased from 187.2 to 203.8 g per capita per week (p = 0.00). Fresh foods such as fruits and vegetables, bread, milk, yogurt, and non-alcoholic beverages, were the most wasted. In July the level of waste was higher for fruit (p = 0.00) while in November was higher for potato products (p = 0.04), pasta (p = 0.00), rice (p = 0.04), legumes (p = 0.01), and soups (p = 0.04). Data collected in July 2021 showed that retired people (p = 0.04), families with children (p = 0.01), particularly young children (9–13 years old) (p = 0.02), wasted less while who live in large town areas (p = 0.00), people with self-perceived limited monetary resources (p = 0.01) and mono-component families (p = 0.00) wasted more. The findings of the present work showed that there are specific population groups that wasted more with a gap between the intentions and the actions. The present data have a particular value posing the roots for the establishment of a food waste surveillance system in Italy.